1998
DOI: 10.1002/j.2161-1874.1998.tb00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Parental Alcoholism to Family‐of‐Origin Functioning and Current Marital Satisfaction

Abstract: This study examined the relationship between parental alcoholism, family-of-origin functioning, and current marital satisfaction. Results indicated family-of-origin functioning is positively related to marital satisfaction. In addition, individuals with alcoholic parents reported lower family-of-origin functioning, and an interaction between gender and parental alcoholism was found for marital satisfaction.M arital satisfaction has been a frequent topic in the professional literature for several decades. A num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…These findings are consistent with results of previous research which indicated that a level of marital satisfaction was relatively lower in spouses with adverse experiences in their families of origin (e.g., parental divorce) (Booth & Edwards, 1989;Wamboldt & Reiss, 1989). Campbell et al (1998) concluded that, although family-of-origin functioning was connected to marital satisfaction and that parental alcoholism was associated with family-of-origin functioning, there was no direct correlation between marital satisfaction and parental alcoholism.…”
Section: Selected Determinants Of Marital Satisfactionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with results of previous research which indicated that a level of marital satisfaction was relatively lower in spouses with adverse experiences in their families of origin (e.g., parental divorce) (Booth & Edwards, 1989;Wamboldt & Reiss, 1989). Campbell et al (1998) concluded that, although family-of-origin functioning was connected to marital satisfaction and that parental alcoholism was associated with family-of-origin functioning, there was no direct correlation between marital satisfaction and parental alcoholism.…”
Section: Selected Determinants Of Marital Satisfactionsupporting
confidence: 91%
“…James L. Campbell et al (1998) conducted a survey on female and male clients from outpatient counselling centres for alcoholics. Participants expressed a wide range of mental health concerns.…”
Section: Selected Determinants Of Marital Satisfactionmentioning
confidence: 99%
“…Children and families contend with a variety of detrimental effects from parental alcoholism (Campbell, Masters, & Johnson, 1998;Deming, Chase, & Karesh, 1996;Hall & Webster, 2002;Harter, 2000;Johnson, 2001;Jones, & Kinnick, 1995). For example, communication in alcoholic families is often more negative than in nonalcoholic families (Sheridan & Green, 1993).…”
mentioning
confidence: 99%
“…Individuals raised in alcoholic homes have reported significantly lower perceived levels of FOO functioning than those who did not report such a history (Campbell et al 1998), and generally children whose parents' marriage ended in divorce report lower marital happiness and feel less positive about their marriages (Glen and Kramer 1987).…”
Section: Family-of-origin Influences On Future Relationship Outcomesmentioning
confidence: 97%